Queens of the Digital Realm: Unveiling of Female Social Media through Personal Branding Analysis - Darsono, Nabila Putri; Ernungtyas, Niken Febrina (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
Personal branding is a crucial aspect of communication, particularly in social media. Someone who can influence others, usually referred to as an influencer, must have positive personal branding from the public perspective. An influencer can come from various industries besides entertainment, including politics and lifestyle. The research was conducted to examine personal branding as displayed by Maria Rahajeng and Tsamara Amany through their Instagram personal account, @tsamaradki, and @mariarahajeng, and to describe the alignment of their personal branding with the eight main concepts of Montoya's concepts. This study employed a postpositivist qualitative research methodology that focused on the personal branding phenomenon formed by the two influencers. This study uses eight main concepts of personal branding Montoya in analyzing content posted by the two influencers. Data was gathered from the influencer’s accounts through feeds, Instagram stories, reels, and comment features. Research results show that the personal branding displayed by Maria Rahajeng and Tsamara Amany differs according to the context of their work, where the two influencers show their respective advantages. Both influencers possess contrasting abilities in various aspects of Montoya’s eight main concepts in personal branding, setting them apart from one another.